Diseases of dairy animals and management - Singh, A. P.; Tripathi, A. K. (Indian Farming, 2018)
For some diseases, the best method of protection is testing prior to purchase. Screening tests can be very useful for avoiding brucellosis, tuberculosis, contagious mastitis and BVD. For Johne’s disease, individual animal screening tests are inadequate and knowledge of the Johne’s disease status of the herd of origin is probably more important. Consideration should be given to entry of new animals, quarantine of new animals, prepurchase vaccination and testing or screening for disease, knowledge of the herd of origin for new purchases, minimization of feed and environmental contamination, disinfection of instruments, minimized contact between sick and healthy cattle or dams and calves, minimized fecal contamination, fly and other insect control programmes,and minimized contact with other species.